Theoretical approximations between Sternberg's Theory of Triarchic Intelligence and Ausubel's Theory of Meaningful Learning: a proposal for evaluating the emergent learning of the Problematized Experimental Activity (PEA) - André Luís Silva da Silva; Paulo Rogério Garcez de Moura; Mariane Lima de Souza (Revista de Ensino de Ciências e Matemática)
In the formal teaching of Natural Sciences, it is verified that experimental activities are developed occasionally, either due to the lack of spaces suitable for their realization, or due to the precarious conditions for teaching, or even due to the lack of preparation and/or disapproval of the teacher in doing so. The Science laboratory, however, if used effectively, is fertile ground for the development of cognitive and metacognitive skills, and for the meaningful learning of scientific concepts, principles and theories. In this regard, carrying out an assessment of the skills developed by students is crucial, with a view to qualifying teaching methods and methodologies. As such, as a theoretical research problem, we seek in this article establish approximations between Sternberg's Theory of Triarchic Intelligence and Ausubel's Theory of Meaningful Learning and, based on the emerging arguments, develop and show Cognitive Performance Indicators, under the domain of conditions for practical, analytical and creative intelligence. Finally, in the light of the Problematized Experimental Activity (PEA), it will be argued about space-time for the application of such indicators, with the purpose of learning evaluation, considering sequential studies and interventions.